Paternal occupational lead exposure and congenital malformations. Issue 5 (October 1992) - Sallmén, M; Lindbohm, M L; Anttila, A; Taskinen, H; Hemminki, K
Abstract : STUDY OBJECTIVE--The aim was to investigate whether occupational exposure to lead in fathers is associated with congenital malformation in their children. DESIGN--The study was a retrospective case-control study, nested within the wives of men biologically monitored for inorganic lead. Information on pregnancy outcome was obtained from medical registers. SUBJECTS--Cases were defined as wives with malformed child during 1973-82. Three age matched controls were selected for each case from the wives who had given birth during 1973-1983. The final study population was 27 cases and 57 controls. MEASUREMENTS AND MAIN RESULTS--Paternal lead exposure was assessed with blood lead measurements and data obtained from a questionnaire. The response rate was 67% among the cases and 76% among the controls. The odds ratio (OR) of congenital malformation for paternal lead exposure was increased (OR 2.4, 95% confidence interval 0.9-6.5), although not reaching statistical significance. The odds ratios varied from 1.9 to 3.2, when adjusted for one potential confounding variable at a time. CONCLUSIONS--Because of the small numbers and low participation, this study offers limited support for the hypothesis that paternal lead exposure is associated with congenital malformation. Further epidemiological studies on the reproductive hazards of paternal lead exposure are needed.